A HIGH GENETIC SIMILARITY AMONG THE SELECTED MANGO (MANGIFERA INDICA L.) GENOTYPES-CULTIVARS DEMONSTRATED BY SSR FINGERPRINTING ASSAY - I. A. Rajwana; T. Shaheen2; A. U. Malik; A. S. Khan; Mahmood-ur-Rahman; M. A. Iqbal; Y. Zafar; Mehboob-ur-Rahman (Journal of Animal and Plant Sciences, 2020)
Mango (Mangifera indica L.) is one of the most important fruit crops worldwide. Mango has a long history of cultivation in Indo-Pak region which resulted in the development of novel regional germplasm as well as many famous mango cultivars. For sustaining the mango production especially in the present scenario of changing climate, it is important to characterize and estimate the genetic divergence among the mango genotypes-cultivars germplasm. To the extent of our knowledge, little efforts have been made to explore the magnitude of genetic divergence among the mango genotypes-cultivars. In this study, the genetic diversity assessments among 32 including 25 local and 7 exotic genotype-cultivars have been calculated using thirty-five simple sequence repeat (SSR) markers. The most informative primer was found Micir-6 while the polymorphism information content (PIC) value of all SSRs was found low, i.e., 0.168 - 0.5. Genetic diversity ranged from 15% to 47% among cultivars with a mean value 30%. The dissimilarity coefficients based unweighted pair group of arithmetic means (UPGMA) was used to make clusters. Mostly East Indian, North Indian and Pakistani cultivars were grouped in one cluster while South Indian and Florida cultivars in other according to the dendogram. The present study would help in taking proactive decision to buffer the spread of any epidemics and will also be helpful in initiating marker-assisted breeding program for developing cultivars with excellent genetics.
Keywords: Genetic Diversity; Indo-Pak; Mangifera indica L.; SSR markers